1997
DOI: 10.1098/rstb.1997.0130
|View full text |Cite
|
Sign up to set email alerts
|

Parietal and hippocampal contribution to topokinetic and topographic memory

Abstract: This paper reviews the involvement of the parietal cortex and the hippocampus in three kinds of spatial memory tasks which all require a memory of a previously experienced movement in space. The ¢rst task compared, by means of positron emission tomography (PET) scan techniques, the production, in darkness, of self-paced saccades (SAC) with the reproduction, in darkness, of a previously learned sequence of saccades to visual targets (SEQ). The results show that a bilateral increase of activity was seen in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 86 publications
(70 reference statements)
5
85
2
2
Order By: Relevance
“…Because we did not investigate the area caudal to the splenium of the corpus callosum, the term "posterior cingulate" cortex (PCC) was used to describe this cortical region rather than the name "retrosplenial" cortex. Anatomical connectivity studies show that the PCC is connected with motor, visual, and subicular cortices, and the anterior thalamus (Berthoz, 1997;Ohnishi et al, 2006), which were areas also examined for C.O. activity in this study.…”
Section: Brain Processingmentioning
confidence: 92%
See 1 more Smart Citation
“…Because we did not investigate the area caudal to the splenium of the corpus callosum, the term "posterior cingulate" cortex (PCC) was used to describe this cortical region rather than the name "retrosplenial" cortex. Anatomical connectivity studies show that the PCC is connected with motor, visual, and subicular cortices, and the anterior thalamus (Berthoz, 1997;Ohnishi et al, 2006), which were areas also examined for C.O. activity in this study.…”
Section: Brain Processingmentioning
confidence: 92%
“…A spatial attention task showed fMRI activation in the PCC that was strongly correlated with the speed of target detection when spatial cues were present (Mesulam et al, 2001). The PCC was also active when subjects were asked to remember visual landmarks and their movements along a previously learned route (Berthoz, 1997). Similarly, Maguire et al (1997) found that the PCC was involved during tasks that required learning a room that contained salient objects and empty rooms only distinguished by their shape, as well as remembering environments recently learned and those very familiar.…”
Section: Introductionmentioning
confidence: 99%
“…The PCC and RSC have long been recognized to be involved in memory access and topographic orientation in human ablation (Valenstein et al, 1987), stroke (Takahashi et al, 1997;Maguire, 2001), and imaging Maguire, 2001;Piefke et al, 2003) studies. The topokinetic memory network includes parietal, insular, cingulate and hippocampal cortices (Berthoz, 1999). Neurons in area 23 of PCC code for the orbital position of the eye and respond to large textured visual fields (Olson et al, 1993(Olson et al, , 1996.…”
Section: Overview Of Posteromedial Cingulate Functionmentioning
confidence: 99%
“…Strokes in right hemisphere RSC/PCC can produce topographic disorientation (Takahashi et al, 1997) as did a splenial glioma (Bottini et al, 1990), while those in the left hemisphere and tumors pressing preferentially on the left RSC produced severe anterograde and retrograde memory impairments including that for verbal and visual information (Valenstein et al, 1987;Rudge and Warrington, 1991). Functional imaging has shown this region is part of a network that mediates topokinetic (spatial) navigation and memory (Ghaem et al, 1997;Maguire et al, 1997;Berthoz, 1997Berthoz, , 1999. Alert monkey studies by Olson et al (1993Olson et al ( , 1996 showed that neurons in the dorsal PCC were active while assessing large visual field patterns and activity was tightly linked to the position of the eye in the orbit and the direction and amplitude of saccadic eye movements.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory stimuli determine how the world is represented in organisms' nervous systems whereas processes underlying actions play only a role on how they intervene on the environment to modify it. This passive view of knowledge is challenged by recent behavioural [2], physiological [3] and brain imaging [4] evidence showing that organisms' internal representations of the world depend on the actions with which they respond to sensory stimuli.…”
Section: Introductionmentioning
confidence: 99%